SOSIALISASI INTEGREATED DIGITAL BUSINESS SEBAGAI PENDORONG DIGITALISASI PRODUK PADA KELOMPOK UMKM BATIK LESTARI KECAMATAN SAWAHAN KABUPATEN MADIUN (Jurnal Abdi Masyarakat, 2022)
Today's digital media opens up huge market opportunities. By applying the right techniques can increase traffic visits to social media. Applying techniques using hashtags, copywriting, and SEO. UMKM Batik Lestari is currently still implementing conventional marketing. So needs assistance and training for Integrated Digital Business. With the Integrated Digital Business method, website media and Instagram social media. When there is no content and only uses the hashtags of the 44 user reachable accounts. Integrated condition no content, the account reachable 57 users. Integrated when there is content with hashtags and copywriting, the accounts reachable by 78 users. Integrated when conditions Use hashtags, copywriting, SEO accounts reached 245 users. The increase in visitor traffic on social media accounts is very significant when applying the right Integrated technique.